2021
DOI: 10.9778/cmajo.20210069
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the efficacy and safety of hydroxychloroquine as outpatient treatment of COVID-19: a randomized controlled trial

Abstract: Eighteen years ago, the severe acute respiratory syndrome (SARS) experience 1-5 highlighted limited knowledge of early treatments for novel pandemic respiratory viruses. With the emergence of SARS-CoV-2, early experience in Wuhan, 6 the Lombardy region of Italy 7,8 and New York City 9 demonstrated the need to suppress severe disease to prevent health system collapse. Hydroxychloroquine, derived from the centuries-old antimalarial medicine quinine, has broad antiviral effects and immunomodulatory properties, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 40 publications
1
35
0
8
Order By: Relevance
“…Overall, 115 studies with 77,128 patients reported the number of patients requiring mechanical ventilation during the study period. We included ACEIs/ARBs, ammonium chloride, azithromycin, bamlanivimab, baricitinib plus remdesivir, bromhexine, budesonide, camostat mesilate, canakinumab, chloroquine, colchicine, convalescent plasma, dexamethasone, doxycycline, favipiravir, hydroxychloroquine, hydroxychloroquine plus azithromycin, hydroxychloroquine plus favipiravir, imatinib, INM005, interferon beta, intravenous immunoglobulin, ivermectin, lopinavir/ritonavir, methylprednisolone, recombinant human GCSF, remdesivir, sarilumab, sofosbuvir plus daclatasvir, sulodexide, tocilizumab, tofacitinib, vitamin D3 and SOC as treatment nodes in the NMA, for which observations came from 84 studies ( 3 , 6 , 22 26 , 28 31 , 35 , 42 , 43 , 46 , 47 , 50 , 53 , 55 , 57 61 , 63 , 64 , 66 , 67 , 71 , 73 77 , 79 , 80 , 82 , 83 , 85 87 , 89 , 92 94 , 96 100 , 102 , 105 107 , 109 , 111 118 , 120 124 , 126 , 128 132 , 134 , 135 , 139 , 140 , 145 , 151 , 152 , 154 156 ). About one-third (26/84) of the included studies were evaluated as low risk ( Supplementary Table 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 115 studies with 77,128 patients reported the number of patients requiring mechanical ventilation during the study period. We included ACEIs/ARBs, ammonium chloride, azithromycin, bamlanivimab, baricitinib plus remdesivir, bromhexine, budesonide, camostat mesilate, canakinumab, chloroquine, colchicine, convalescent plasma, dexamethasone, doxycycline, favipiravir, hydroxychloroquine, hydroxychloroquine plus azithromycin, hydroxychloroquine plus favipiravir, imatinib, INM005, interferon beta, intravenous immunoglobulin, ivermectin, lopinavir/ritonavir, methylprednisolone, recombinant human GCSF, remdesivir, sarilumab, sofosbuvir plus daclatasvir, sulodexide, tocilizumab, tofacitinib, vitamin D3 and SOC as treatment nodes in the NMA, for which observations came from 84 studies ( 3 , 6 , 22 26 , 28 31 , 35 , 42 , 43 , 46 , 47 , 50 , 53 , 55 , 57 61 , 63 , 64 , 66 , 67 , 71 , 73 77 , 79 , 80 , 82 , 83 , 85 87 , 89 , 92 94 , 96 100 , 102 , 105 107 , 109 , 111 118 , 120 124 , 126 , 128 132 , 134 , 135 , 139 , 140 , 145 , 151 , 152 , 154 156 ). About one-third (26/84) of the included studies were evaluated as low risk ( Supplementary Table 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven new RCTs were retrieved by the SLR search update, adding to the existing eight RCTs on HCQ included in the previous SLR. Out of these 11 new studies, 4 have been stopped early for futility, 4–7 2 have been stopped for harmful effects of one or several compounds in the intervention arms, 8 9 and 1 is underpowered, 10 hence the results are not described in this manuscript. Out of the six studies that included patients with moderate to severe COVID-19, one compared HCQ to chloroquine or ivermectine showing no efficacy on death, progression to invasive mechanical ventilation (IMV) or admission to intensive care unit (ICU) at day 90.…”
Section: Resultsmentioning
confidence: 99%
“…Third, there was no data on ICU admissions, need of mechanical ventilation, or specific adverse events. Fourth, four of the five RCTs [19][20][21][22] had fewer patients randomized than originally planned; this may have been resulted in lack of power to detect effects of hydroxychloroquine on outcomes. Finally, we did not evaluate the effect of adding azithromycin to hydroxychloroquine in our study.…”
Section: Discussionmentioning
confidence: 99%
“…After removing duplicates and P r e p r i n t applying our inclusion and exclusion criteria (Fig. S1), we identified five RCTs [18][19][20][21][22] (n=1848) which were all homogenous enough to warrant meta-analyses.…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation